Perancangan Eduwisata Daur Ulang Sampah/Limbah di Jakarta Barat dengan Pendekatan Arsitektur Ramah Lingkungan - Putri Buana Kusumastuti; Putri Suryandari; Sri Kurniasih (MAESTRO, 2020)
ABSTRACT Recycle Educational Tour is a place for people to aware of the importance environment from the trash around us, Environmentally Friendly Architecture will applied as an example for love the environment with safe the energy in place and proper arragement. In West Jakarta is an Area to needs attention of Trash production everyday. Trash Volunteers in West Jakarta is a lot, and the target is local society and student of school which required knowledge of protecting the environment. Keyword : Recycle, West Jakarta, Environmentally Friendly Architecture